Loser Takes All: Graham Greene’s Theological Puzzle Box - Comerford, Peter J. (New blackfriars, 2024)
Graham Greene’s novella Loser Takes All has been unfairly ignored in the critical literature. Rather than the mere frivolity it is taken to be, it is a humorous examination of some serious theological issues. By means of an inversion of Pascal’s Great Wager, Greene makes the case that attempts to rationalize the mystery that is the object of our faith will cheapen and diminish that faith. In the course of so doing, he alludes to and has fun with his earlier works, particularly Brighton Rock, and critiques the inversion of the Wager by Albert Camus. He shows the influence of Miguel de Unamuno, who years later would influence Greene’s Monsignor Quixote. Greene also invokes a poem by Charles Baudelaire, which Greene has quoted in many works, that the possibility of damnation adds meaning to life, though it may drift into what von Balthasar called Greene’s indulgence of the mystique of sin.